Desarrollo de habilidades cognitivas en los estudiantes de primero y segundo año de bachillerato del Colegio Dr. Modesto Chávez Franco del cantón Santa Rosa, provincia de El Oro 2012. - Espinoza Ramos, María Belén (2013)
The first part includes the theoretical and scientific guidelines underpinning the theoretical framework that emerges from the variables under study, to support research from concepts, definitions and educational contribution that will allow viable work with solid arguments.